Association between Neurofibromatosis Type 1 and Breast Cancer: A Report of Two Cases with a Review of the Literature - Yoon Nae Seo; Young Mi Park (Case Reports in Medicine)
Neurofibromatosis type 1 (NF1) is one of the most common genetic diseases in humans and is associated with various benign and malignant tumors, including breast cancer. However, an increased risk of breast cancer in NF1 patients has not been widely recognized or accepted. Here, we report two cases of breast cancer in NF1 patients and review the literature on the association between NF1 and breast cancer.